MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU PADA SMP NEGERI 1 BATEE KECAMATAN BATEE KABUPATEN PIDIE - Hendon, Cut Zahri Harun, Nasir Usman. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
ABSTRACT:The purpose of this study was to find out the program, implementation, evaluation, and obstacles faced by the principal in improving the professional competence of teachers at State Junior High School 1 Batee of Batee Sub-district of Pidie Regency. This research used descriptive method with qualitative approach. The technique of data collection used were observation, interview, and documentation study. Subjects of the research were principal, vice principals, chairman of MGMP (Teacher Network), teachers, school supervisors, and school committees. Data were analyzed by means of data reduction, data display, conclusion drawing, and data verification. The results showed that: (1) Programs are arranged at the beginning of each school year by the school development team and has not been well documented and tidy. The planned program was the preparation of lesson plans, implementation of learning, evaluation of learning, supervision of classroom, implementation of MGMP and procurement of instructional media; (2) Activities carried out not all listed on a standard instrument, the schedule of activities was not all according to plan and the frequency of the activities was not in accordance with the planned program that has been prepared; (3) The evaluation was conducted at the end of each semester and served as a follow-up program to determine the advanced program. The evaluation results were presented to teachers, both individually and in groups; and (4) obstacles faced were: the teachers did not master ICT well, they did not master the subject matter, they rarely applied the learning method, the principal had too much workload, and the absence of a standard school program.KEYWORDS: management, planning, actuating, evaluating, principal and teacher professional competency ABSTRAK: Tujuan penelitian ini untuk mengetahui program, pelaksanaan, evaluasi, dan hambatan-hambatan yang dihadapi kepala sekolah dalam meningkatkan kompetensi profesional guru pada SMP Negeri 1 Batee Kecamatan Batee Kabupaten Pidie. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data melalui: observasi, wawancara, dan dokumentasi. Subjek penelitian adalah: kepala sekolah, wakil kepala sekolah, ketua MGMP, guru, pengawas, dan komite sekolah. Data dianalisis dengan cara: reduksi data, display data, mengambil kesimpulan, dan verifikasi data. Hasil penelitian menunjukkan: (1) Program disusun pada setiap awal tahun pelajaran oleh tim pengembangan sekolah belum terdokumentasi dengan baik. Program yang direncanakan berupa: penyusunan RPP, pelaksanaan pembelajaran, evaluasi pembelajaran, supervisi kelas, melaksanakan MGMP, dan pengadaan  media pembelajaran; (2) Kegiatan yang dilaksanakan belum semuanya tercantum pada instrumen yang baku, jadwal pelaksanaan kegiatan belum semuanya sesuai rencana dan jumlah kegiatan tidak sesuai dengan perencanaan program yang sudah disusun; (3) Evaluasi dilaksanakan pada setiap akhir semester dan dijadikan sebagai tindak lanjut dalam menentukan program lanjutan. Hasil evaluasi disampaikan kepada guru, baik secara individual maupun secara kelompok; dan (4) Hambatan-hambatan yang dihadapi adalah guru kurang menguasai ICT, kurang menguasai materi pelajaran, jarang menerapkan metode pembelajaran, banyaknya tugas kepala sekolah, dan belum adanya program sekolah yang baku.KATA KUNCI: manajemen, perencanaan, pelaksanaan, evaluasi, kepala sekolah dan kompetensi professional guru